The Effect Of Environmental Performance On Company Value With Financial Performance And Corporate Governance As Intervening Variables - Rahayu Safitri Mutmainah; Riana Sitawati (Institut Nalanda, 2023)
This study examines the effect of environmental performance on company value by mediating financial performance and good corporate governance. The research objective is to find empirical evidence about (1) the influence of environmental performance on company value, (2) the influence of environmental performance on financial performance, (3) the influence of environmental performance on good corporate governance. (4) the influence of financial performance on company value. (5) the influence of Good Corporate Governance on company value, (6) the influence of environmental performance on company value by mediating financial performance, (7) the influence of environmental performance on company value by mediating Good Corporate Governance. Environmental performance is measured using PROPER and company value is measured using Price Book Value, for the mediating variable Environmental Financial Performance is measured using ROA, Good Corporate Governance is measured using institutional ownership. The object of this research is a group of manufacturing industries listed on the Indonesia Stock Exchange (IDX) in the 2015-2019 period. The research sample was 55 companies with 5 years of observation. The data analysis test tool used warp PLS 5.0 software for each variable. The test results show that environmental performance has no significant effect on company value, environmental performance has a significant and positive effect on financial performance, environmental performance has a significant and positive effect on institutional ownership, financial performance has a significant and positive effect on company value, institutional ownership has no effect on company value. , Environmental Performance has an effect on company value through Financial Performance, Environmental Performance has no effect on company value through Institutional Ownership.